Development of the Revision Hip Complexity Classification using a modified Delphi technique. (2022) - Leong, J. W. Y.; Singhal, R.; Whitehouse, M. R.; Howell, J. R.; Hamer, A.; Khanduja, V.; Board, T. N.
No abstract available